USIA MATURITAS PERNIKAHAN DENGAN SIKAP IBU DALAM PEMBERIAN AIR SUSU IBU EKSKLUSIF PADA BAYI USIA 0-6 BULAN DI KECAMATAN PANTI KABUPATEN JEMBER: USIA MATURITAS PERNIKAHAN DENGAN SIKAP IBU DALAM PEMBERIAN AIR SUSU IBU EKSKLUSIF - Hasanah, Umi Nur; Susanto, Tantut; Rasni, Hanny; Fauziah, Wahyuni (JURNAL SVASTA HARENA RAFFLESIA, 2024)
Married women who birthing at aged 15-19 years contributed to non-exclusive breastfeeding. Coverage of babies getting exclusive breastfeeding is still not optimally that influenced by the relatively unstable emotionally of a teenage mother. The aim of this study was to analyze the relationship between maturity of aged marriage and the attitude of exclusive breastfeeding among mothers with infants aged 0-6 months at Panti District Jember Regency. A cross-sectional study was conducted among 320 mothers using stratified random sampling. A self-administered questionnaire was used to assess mothers aged of marriage and the attitude of exclusive breastfeeding. Data were analyzed by the Chi-Square (0,05). The results showed that the median of the aged marriage of mothers was 22 aged. The attitude of exclusive breastfeeding mothers was 91% of enough. The analysis with chi-square showed that there was no relationship between age of maturity with the attitude of exclusive breastfeeding in infants aged 0-6 months (p-value > 0,05). However, There was a relationship between the age of marriage maturity and the mother who believes that the mothers’ age affects her ability to breastfeed exclusively (X2=9,848; p-value=0,007. There was also a relationship between the age of maturity and breastfeeding which is easier to digest than formula milk (X2=4,148; p-value=0,042). Therefore, health counselors could provide to mothers about the limit of aged for marriage and pregnant for continuiting the exclusively breastfeeding fot their babies in the future.